Uma discussão sobre os conceitos de fronteira e território no ensino fundamental, anos iniciais, de Geografia - Rodrigues, Aline de Lima [UNESP] (2015)
The guiding concepts of Geographical Science have been submitted to significant theoretical and methodological reviews throughout the history of geographical thinking. However, regarding geography teaching, discussing these changes is still recent and it requires, is some cases, theoretical knowledge for a more adequate analysis. The present research is focused in analyzing the concepts of border and territory in basic education - early grades of Geography, understanding the relations of power and sovereignty that define territories and national borders as something beyond a simple political-administrative limit. Hence, concepts of border and territory were analyzed in didactic books, which were selected by the PNLD (Brazilian National Textbook Program) (2011), seeking to: (a) discuss the meaning of border and territory, facing transformations in the organization of the geographical space, and (b) analyze the concepts adopted and the meanings of border and territory in basic education, early grades of Geography. Structurally, the research was performed in stages. First, structuring and operation of core concepts were executed through the reading of specialized works. Later, a research was carried out on the concepts of border and territory in the collections selected: Novo Interagindo - com a Geografia, Projeto Prosa, Porta Aberta - Geografia, and Projeto Eco, all collections from 2011. The final analysis of the results was led by the theoretical approach of the theme, regarding both the etymological evolution of border and territory concepts and the approach in didactic Geography books for basic education